STRATEGI PENGUATAN PERAN KELEMBAGAAN DESA DALAM PENINGKATAN KETAHANAN PANGAN DI DESA KENDALBULUR, KABUPATEN TULUNGAGUNG - Riya Irawati Irawati; Reza Pirgianta Ginting; Neneng Sri Rahayu (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2023)
Based on the composite food security index, Tulungagung Regency is classified as good or highly resilient to vulnerabilities. However, there are still issues within the institutional framework of Kendalbulur Village, particularly the need for more human resources in village governance. This study aims to illustrate the role of village institutions in managing food security and the strategies for strengthening the governance institutions. Data collection for this research was conducted through document review, interviews, and field observations. The analysis includes an analysis of village potential, village governance institutions, village budget management, regulations, village development, village autonomy, and strategies for strengthening the role of village institutions in improving food security using SWOT analysis and the IFAS-EFAS matrix. The results of this study demonstrate the crucial role of village institutions in managing food security. Furthermore, the Rapid Growth Strategy is the strategy for strengthening the role of Kendalbulur Village institutions in improving food security. Therefore, Kendalbulur Village needs to consistently implement regulations and institutional support to enhance agriculture, fishery, livestock farming, and tourism while maximizing the potential of these sectors.